Avian IgY antibodies: characteristics and applications in immunodiagnostic - Munhoz,Lívia Silveira (2014)
Immunoglobulin Y (IgY) is the major antibody isotype in birds, reptiles, amphibia, and lungfish, playing a similar biological role as mammal IgG. Due to its phylogenetic distance, immune diversification and presence in the egg yolk, IgY provide a number of advantages in immunodiagnostic compared to IgG from mammals. Moreover, IgY production is in agreement with international efforts to reduce, refine and if possible, to replace animals in experimentation, contributing substantially in favor of animal welfare. This article presents an overview about structural and functional features, production and applications of IgY in immunodiagnostic, as well as the advantages of chicken antibodies use.